FAKTOR-FAKTOR KESULITAN BELAJAR DAN DAMPAKNYA TERHADAP MOTIVASI BERPRESTASI PADA MATA KULIAH STATISTIKA MATEMATIKA I - Gunawan, Muhammad Ali; Fitri, Amalia (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The ability of students to apply the concepts of statistics in problem solving is low. It is not only caused by factors lecturers but also socio-economic, environmental, family, campus environment, and so on. These factors need to be assessed so that learning objectives can be achieved optimally. Issues that will be examined are: 1) Whatis the factor that can affect difficulty of learning statistics 1 in the fourth semester students of mathematics education courses and science teacher education faculty Pekalongan University Academic Year 2012/2013? 2) How do these factors influence the achievement motivation of fourth semester students of mathematics education courses and science teacher education faculty Pekalongan University Academic Year 2012/2013? The study population was all students of fourth semester mathematics education courses. The sampling technique used is proportional sampling technique and simple random sampling. Data analysis techniques used in this study is a factor and multiple regression analysis (multiple regression). The results showed that the factors that affect difficulty learning statistics 1 are internal factors and external factors. Internal factors include the factors physical / health and psychological factors. The external factors include: a) family environment, b) the campus environment, and c) society. Â  Kata Kunci :Kesulitan Belajar, Motivasi Berprestasi, Statistik Matematika 1